Effect of metal oxide based TiO2 nanoparticles on anaerobic digestion process of lignocellulosic substrate. (15th January 2020) - Ghofrani-Isfahani, Parisa; Baniamerian, Hamed; Tsapekos, Panagiotis; Alvarado-Morales, Merlin; Kasama, Takeshi; Shahrokhi, Mohammad; Vossoughi, Manouchehr; Angelidaki, Irini
Abstract: Lignocellulosic materials are recalcitrant to bioconversion, due to their rigid physiochemical structure. In this work, the effects of Fe2 O3 –TiO2 and NiO–TiO2 nanoparticles (NPs) and FeCl3 and NiCl2 salts, on the anaerobic digestion (AD) of wheat straw have been investigated. For this purpose, metal oxide-TiO2 NPs were synthesized and fully characterized. Results showed that addition of 0.252 mg of NiO–TiO2 /g total solids (TS) to batch assays resulted in increase of soluble chemical oxygen demand (COD) and 67% increase in volatile fatty acids (VFAs) concentration compared to control tests during the first 4 days of experiments. These results indicate that hydrolysis and acidogenesis rates have been enhanced due to addition of NPs. No significant effects have been observed in soluble COD and VFAs concentrations compared to control experiments by adding salts to the batch assays. Addition of NPs or salts led to an increase in methane production rate during the first 4 days of experiments. Highlights: TiO2 nanoparticles (NPs) coated with Fe2 O3 or NiO were synthesized and characterized. The effects of trace metals were tested on anaerobic digestion of wheat straw. Up to 13% increase in soluble COD is observed due to increase of hydrolysis rate. Total VFAs production rate increased up to 67% using NPs. NPs and salts boosted methane production rate up to 21.1% and 29%, respectively.